2022
DOI: 10.3390/antiox11081611
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 Modulates Endothelial Mitochondrial Redox State during Insulin Resistance

Abstract: Emerging evidence indicates that defects in sirtuin signaling contribute to impaired glucose and lipid metabolism, resulting in insulin resistance (IR) and endothelial dysfunction. Here, we examined the effects of palmitic acid (PA) treatment on mitochondrial sirtuins (SIRT2, SIRT3, SIRT4, and SIRT5) and oxidative homeostasis in human endothelial cells (TeloHAEC). Results showed that treatment for 48 h with PA (0.5 mM) impaired cell viability, induced loss of insulin signaling, imbalanced the oxidative status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The improved lipid metabolism conferred by LR may be related to reduce ERS. In the other two studies, LR also improves lipid metabolism by regulating other pathways, which is consistent with this study [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The improved lipid metabolism conferred by LR may be related to reduce ERS. In the other two studies, LR also improves lipid metabolism by regulating other pathways, which is consistent with this study [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Bioactive compounds of milk, especially buffalo milk, have been described as epi-nutrient for cancer prevention. In SW480 and SW620 CRC cells δ-valerobetaine, a constitutive milk metabolite with antioxidant, anti-inflammatory, and anti-diabetic activities, impaired cell viability in a time-dependent way, blocked cell cycle at G2/M increasing the expression of cyclin A and cyclin B protein [ 14 , 17 , 47 ]. Caspase-3 activation, together with loss in mitochondrial membrane potential and SIRT3 downmodulation, enhanced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent data showed that δ-valerobetaine also protected ECs against PA-induced insulin resistance (IR) by limiting the inhibitory phosphorylation of IRS1 and restoring phosphorylated Akt expression levels. In particular, δ-valerobetaine reduced oxidative stress and cytokine levels, restored the expression levels of mitochondrial sirtuin 3, and attenuated pyroptosis and autophagy [ 32 ]. Further studies are undoubtedly necessary for a deeper understanding of biological effects caused by bioactive compounds identified in the milk and/or their mixtures in the prevention of EC inflammation.…”
Section: Discussionmentioning
confidence: 99%